Measuring investor sentiment with mutual fund flows - Ben-Rephael, Azi; Kandel, Shmuel; Wohl, Avi (Journal of Financial Economics, 2012)
We investigate a proxy for monthly shifts between bond funds and equity funds in the USA: aggregate net exchanges of equity funds. This measure (which is negatively related to changes in VIX) is positively contemporaneously correlated with aggregate stock market excess returns: One standard deviation of net exchanges is related to 1.95% of market excess return. Our main new finding is that 85% (all) of the contemporaneous relation is reversed within four (ten) months. The effect is stronger in smaller stocks and in growth stocks. These findings support the notion of “noise” in aggregate market prices induced by investor sentiment.